Dismissing chronic illness: A qualitative analysis of negative health care experiences. Issue 3 (4th March 2019) - McManimen, Stephanie; McClellan, Damani; Stoothoff, Jamie; Gleason, Kristen; Jason, Leonard A.
Abstract: In the US, medical training is inadequate regarding the symptomatology, prognosis, and treatment for myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS). As a result, many physicians lack the appropriate level of knowledge about effective methods for ME and CFS symptom reduction and often suggest inappropriate treatments, such as increased exercise or psychiatric services. The authors' purpose in this study was to analyze negative patient experiences with health care professionals. Patients with ME and CFS who reported experiencing a dismissive physician attitude were asked to detail the encounter via open-ended response on an international, online survey. Participant responses were thematically coded and analyzed using processes outlined by Patton. Emergent themes related to perceived physician attitudes and how they impact patient wellbeing are described and their implications discussed. Additionally, we highlight suggestions for how the health care system can effectively approach this often marginalized patient group.